Thermal Non‐Oxidative Aromatization of Light Alkanes Catalyzed by Gallium Nitride1. Issue 51 (21st October 2014) - Li, Lu; Mu, Xiaoyue; Liu, Wenbo; Kong, Xianghua; Fan, Shizhao; Mi, Zetian; Li, Chao‐Jun
Abstract The thermal catalytic activity of GaN in non‐oxidative alkane dehydroaromatization has been discovered for the first time. The origin of the catalytic activity was studied experimentally and theoretically. Commercially available GaN powders with a wurtzite crystal structure showed superior stability and reactivity for converting light alkanes, including methane, propane, n‐butane, n‐hexane and cyclohexane into benzene at an elevated temperature with high selectivity. The catalyst is highly robust and can be used repeatedly without noticeable deactivation.